Validating Dissociative Experience Scale (DES) in a Greek sample. Issue 5 (20th October 2021) - Tzikos, Anthimos; Arvaniti, Aikaterini; Kalamara, Eleni; Vorvolakos, Theofanis; Kafalis, Georgios; Samakouri, Maria; Livaditis, Miltos
ABSTRACT: This study aimed to validate the Greek version of the Dissociative Experience Scale (DES). A sample of 340 psychiatric outpatients and controls was selected. Part of the sample went through a retest procedure after a two-week period. Due to the absence of equivalent tests, the Multiscale Dissociation Inventory (MDI), the Structured Clinical Interview for DSM-IV-Dissociative Disorders Revised (SCID-D-R), and the Zung Self-Rating Anxiety Scale were used. Explanatory factor analysis was performed, resulting in a 28-item scale; the analysis revealed four factors, explaining 61% of total variation: Depersonalization, Amnesia, Absorption, and Miscellaneous. Cronbach's alpha coefficient for the DES was 0.95. Intraclass correlation coefficient (ICC) of the total score between the first and second interview was 0.84. Concurrent and convergent validity, as assessed by correlations with clinical assessment used as a "gold standard, " (0.77), MDI (0.96), and Zung scale (0.75) were satisfactory to excellent. The total score on the DES was significantly higher in the clinical sample than in the controls (17.8 ± 16.2 vs. 5.8 ± 7.2, p < .001), indicating high discriminant validity. After the ROC analysis was run, the best compromise between sensitivity/specificity was achieved at the value of 20. The Greek version of the DES is a reliable and valid tool suitable to assess dissociation in clinical and healthy populations.